Comparative tolerability of targeted therapies in pulmonary hypertension - Magdalena Jasińska-Stroschein; Karolina Stawarczyk; Anna Stępień; Daria Orszulak-Michalak (Archives of Medical Science, 2020)
Introduction The objective of this study was to estimate the safety profile of pulmonary hypertension-specific therapies using placebo-controlled and active comparator trials.